PEMBELAJARAN CONTROVERSIAL ISSUES DALAM MENINGKATKAN KEMAMPUAN KOGNITIF MAHASISWA PADA MATA KULIAH KAPITA SELEKTA SEJARAH INDONESIA - Suwarni Suwarni; Emusti Rivasintha; Yuver Kusnoto (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
The general objective in this research is “to know the application ofcontroversial issue model in improving cognitive ability in Kapita SelektaSejarah Indonesia courses”. This reseach used classroom action researchmethod. Located at Prodi Pendidikan Sejarah IKIP PGRI Pontianak. Subject ofresearch were student that requires 22 people. The design of this researchconsists of planning, implementation, observation and reflection. Datacompletion technique used is direct observation, measurement, anddocumentary. Application of controversial learning model showing the resultthat it can improve students' cognitive abilities in Kapita Selekta SejarahIndonesia. Planning the application of controversial issue model to improvestudents cognitive ability in Kapita Selekta Sejarah Indonesia courses in ProdiPendidikan Sejarah IKIP PGRI Pontianak, has been done well. This is indicatedby the learning process run in accordance with the implementation plan oflearning. The material presented by the lecturer attract the attention of thestudents. The steps of learning model controversial issue has been done well.There are student activeness in asking and replied and they are breave toexpressed his opinion throught answer issues that were given. The timeallocation goes as planned.Keywords: controversial issues, history learnings, cognitive abillity